1985
DOI: 10.1111/j.1558-5646.1985.tb00417.x
|View full text |Cite
|
Sign up to set email alerts
|

ADAPTIVE RADIATION AND GENETIC DIFFERENTIATION IN HAWAIIAN BIDENS

Abstract: The genus Bidens (Asteraceae) has undergone extensive adaptive radiation on the Hawaiian Islands. The 19 species and eight subspecies endemic to Hawaii exhibit much more morphological and ecological differentiation than the continental members of the genus. However, the Hawaiian taxa have the same chromosome number and retain the capacity to interbreed in all possible combinations. Twenty-two populations of 15 Hawaiian taxa and four populations of American taxa were compared at 21 loci controlling eight enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
67
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(77 citation statements)
references
References 23 publications
10
67
0
Order By: Relevance
“…Lowrey & Crawford (1985) found very little isozymic divergence among seven species of Tetramolopium, with a mean genetic identity of 0.95. Similar results were obtained for six species from two of the three recognized subgenera of the genus Dendroseris which is endemic to the Juan Fernandez Islands, Chile (Crawford et a!., 1987a (Helenurm & Ganders, 1985). It has been suggested that congeneric species of insular plants may differ by more conspicuous morphological features than their counterparts on continents in spite of very little genetic divergence (Crawford et a!., 1 987b).…”
Section: Little Genetic Divergence Among Populations Ofsupporting
confidence: 70%
See 1 more Smart Citation
“…Lowrey & Crawford (1985) found very little isozymic divergence among seven species of Tetramolopium, with a mean genetic identity of 0.95. Similar results were obtained for six species from two of the three recognized subgenera of the genus Dendroseris which is endemic to the Juan Fernandez Islands, Chile (Crawford et a!., 1987a (Helenurm & Ganders, 1985). It has been suggested that congeneric species of insular plants may differ by more conspicuous morphological features than their counterparts on continents in spite of very little genetic divergence (Crawford et a!., 1 987b).…”
Section: Little Genetic Divergence Among Populations Ofsupporting
confidence: 70%
“…Narrow genetic divergence at isozyme loci among different insular taxa was also reported for Terramolopium (Lowrey, 1981), Bidens (Ganders & Nagata, 1984;Helenurm & Ganders, 1985) and the silversword alliance of species belonging to the genera Argyroxiphium, Dubautia, and Wilkesia (Carr, 1985a,b;Witter & Carr, 1988) from the Hawaiian islands. Lowrey & Crawford (1985) found very little isozymic divergence among seven species of Tetramolopium, with a mean genetic identity of 0.95.…”
Section: Little Genetic Divergence Among Populations Ofmentioning
confidence: 98%
“…If this view is correct, as the cpDNA data suggest, then evolutionary diversification and spread of the tetraploid taxa after polyploidization has been relatively rapid. This interpretation would not be unprecedented, as others have noted an "uncoupling" of molecular and morphological evolution with respect to both cpDNA (28,39) and isozyme (45)(46)(47) divergence.…”
Section: Resultsmentioning
confidence: 97%
“…This is probably because it is generally assumed that intraspecific diversity in the populations of island endemic plants is very low (Barrett and Husband, 1990), which seems quite logical, given that the lack of resolution in DNA-based phylogenies is a common problem in phylogenetic studies of island plant radiations. Hence, the intraspecific genetic diversity data are mostly based on allozyme diversity (Helenurm and Ganders, 1985;Weller et al, 1996;Marr and Bohm, 1999), which may be quite misleading due to possible non-neutrality of charge changing amino-acid replacements creating allozyme diversity (Hudson et al, 1994;Veuille and King, 1995;Eanes et al, 1996;Filatov and Charlesworth, 1999). Here, we reported one of the first DNA sequence-based estimates of genetic diversity in Hawaiian plants.…”
Section: Discussionmentioning
confidence: 99%